Mengajarkan Shalat Pada Anak Usia Dini Dalam Masa Social Distancing Covid-19 ¬Perspektif Hadis - Nisaul Jannah; Muhammad Alfatih Suryadilaga (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Teaching Prayers to Early Children in the Covid-19 Social Distancing Period – the Perspective of HadithsTeaching prayers to children is parents’ and educators’ obligation that must be done as early as possible. By teaching prayers since an early age, it is hoped that children can develop optimally in terms of physical, spiritual, and intellectual aspects, so that they grow into a generation with character. With the current outbreak of Covid-19, the education and teaching processesare experiencing a number of obstacles because children cannot interact directly with people other than their parents. This article aimed to describe how to teach prayers to early children based on the guidance of the Prophet Muhammad’s hadiths, especially during the social distancing period of Covid-19. The research in this article used a qualitative method with a descriptive analysis approach taken from a variety of document data and in-depth observations. The research revealed that teaching prayers to early children based on the Prophet Muhammad’s hadithsdeployed exemplary methods, habituation, advice, attention and monitoring, and punishment. Last but not least, parents and educators also provided educational materials such as religious, social, physical, moral and intellectual education